Platelet Activity And Some Immunological Findings In Atherosclerosis and Coronary Heart Disease - AI-Assaf, A.I.S (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The platelet activity and some immunological aspects of coronary heart disease CIID were investigated by employing platelet count and serum levels of IgG,IgM and lgA,C3 and C4.Three groups of patients were investigated : patients with ischemic heart disease IHD, patients with lliD+hypcrtension and patients with IHD+unstable angina.The results revealed that the mean of platelets (mm’) was significantly reduced in IHD+unstable angina group 2.72.L I.l2 compared with conrol b’TOUp 8.13Â±2.72. With respect to the immunological study, the re;;ults revealed that lgG level (mg/dl) was significantly reduced in UIDhypertension group 1113.70Â±8.81 and in LHD+unstable angina 857.85Â±17.78 compared with control group 1279.33Â±22.2S.The same effect was observed on IgM,in IHOgroup, the mean was 114.47Â±4.40 and in UID+hypertension group was 122.1 0Â±5.32 compared with control group 177.25Â±4.86.The mean of complement component C3 was significantly increased in IHD+ hypertension group 197.92.%6.56, also in IHD+unstable angina group 150.750Â±1 0.78 compared wih control group I 02.79Â±I0.38.